Active Roles of Tumor Stroma in Breast Cancer Metastasis - Zahraa I. Khamis; Ziad J. Sahab; Qing-Xiang Amy Sang (International Journal of Breast Cancer)
Metastasis is the major cause of death for breast cancer patients. Tumors are heterogenous cellular entities composed of cancer cells and cells of the microenvironment in which they reside. A reciprocal dynamic interaction occurs between the tumor cells and their surrounding stroma under physiological and pathological conditions. This tumor-host communication interface mediates the escape of tumor cells at the primary site, survival of circulating cancer cells in the vasculature, and growth of metastatic cancer at secondary site. Each step of the metastatic process is accompanied by recruitment of stromal cells from the microenvironment and production of unique array of growth factors and chemokines. Stromal microenvironment may play active roles in breast cancer metastasis. Elucidating the types of cells recruited and signal pathways involved in the crosstalk between tumor cells and stromal cells will help identify novel strategies for cotargeting cancer cells and tumor stromal cells to suppress metastasis and improve patient outcome.